Pemanfaatan Limbah Serat Alam Kulit Buah Kelor Sebagai Papan Komposit yang Diperkuat Polimer Unsaturated Polyester Resin - Jayadin, Jayadin; Nisa, Kartini Rahman; Siti Zuraidah; Leto, Kristina Tresia; Coa, Sri Astuti Rahman; Nurhadyati, Nurhadyati; Mujiburohman, Muhammad; Hikmatiar, Hamzarudin (Universitas Ibn Khaldun, 2025)
The use of Composite Materials with natural fiber reinforcement is starting to be widely known in the manufacturing industry, environmentally friendly and recyclable materials. Composites are made to obtain lightweight structures, have higher strength or stiffness, energy absorption and design, have low prices and natural fibers are also easy to obtain, especially moringa fruit skin which is very abundant in the East Nusa Tenggara region, especially in Sikka Regency. This study aims to determine the Bending strength, impact energy and seawater absorption capacity. The research materials are moringa fruit skin fiber and polyester resin. Moringa fruit skin fiber is a waste that is rarely used so it can be a serious waste. This specimen is used with the Cold Compressing Molding method (Molds that are loaded at room temperature). The results of the study showed optimal conditions at a volume fraction of 25%, providing the highest Bending strength of 8,888 MPa, the highest impact energy of 0.196 J / mm2, and the lowest seawater absorption value of 0.79%.